Wandering the barren deserts of Iran: Illuminating high mobility of the Asiatic cheetah with sparse data - Farhadinia, M; Gholikhani, N; Behnoud, P; Hobeali, K; Taktehrani, A; Hosseini-Zavarei, F; Eslami, M; Hunter, L (Elsevier, 2016)
Mammalian species inhabiting arid landscapes exhibit various levels of mobility in order to cope with unpredictable spatiotemporal dispersion of resources. However, the space use and ranging behavior of many species in drylands is poorly understood, especially for large carnivores in Asia. Accommodating the long-distance movements of mammalian carnivores is a major challenge in conservation, particularly for threatened and highly mobile species. The Asiatic cheetah Acinonyx jubatus venaticus, a critically endangered subspecies found only in arid areas of Iran, exhibits high levels of mobility. In the absence of satellite collars, this paper outlines ranging patterns of the majority of the Asiatic cheetah's known population. A total of 17 independent cheetahs (11 males; 6 females) were detected with camera traps that were deployed on eight reserves between January 2011 and May 2016. The animals displayed extensive movements (up to 217 km between furthest known locations) and at least nine adult cheetahs were known to move between multiple reserves in central Iran. This mobility may follow a “nomadic” ranging pattern, a non-sedentary behavior with irregular timing and movement directions. The ranging behavior documented here must be considered when designing monitoring efforts to determine population and occupancy trends for this wide-ranging elusive carnivore. Although preliminary, our results show that improving protection beyond the current network of cheetah reserves, particularly along corridors, should be a top priority to safeguard the persistence of the Asiatic cheetah.